Do Sleep Time and Duration Affect the Development of Prehypertension in Undergraduate Medical Students? An Experience from a Tertiary Care Hospital in Kolkata - Ali, Sayan; Karmakar, Samit; Chakraborty, Arup; Ghosh, Saptarshi (Sleep Science, 2024)
Introduction and Objective Hypertension is an evolving public health challenge at present, and it is preceded by a prehypertensive stage. Irregular sleep duration and pattern have been found to be linked with cardiovascular diseases. Medical students are highly vulnerable to low quality sleep due to pressure regarding the academic curriculum and poor lifestyle. The present study aimed to estimate the prevalence of prehypertension, describe the risk factors and sleep patterns of undergraduate medical students, and determine the association, if any, involving sleep time and duration and prehypertension.Materials and Methods Data was collected from 254 undergraduate medical students via the Pittsburgh Sleep Quality Index (PSQI) questionnaire and a self-structured questionnaire. The frequency of events was established and the Chi-squared and t-tests were applied to determine the association. Finally, regression analysis was performed to determine the correlation.Results Male sex, high body mass index (BMI), poor sleep quality, and night sleep duration shorter than 5 hours were found to be significant risk factors for the development of prehypertensive condition (prevalence of 42.5%). However, there were no statistically significant associations regarding prehypertension and family history, junk food and salt intake, physical activity and daytime napping, bedtime, and wake-up time. Night sleep duration shorter than 5 hours presented an odds ratio of 4.713 (p = 0.010) for the development of prehypertension after adjusting for other risk factors, such as male sex, sleep quality, and high BMI.Discussion and Conclusion A high prevalence of prehypertension (42.5%) was noted among undergraduate medical students. Night sleep duration shorter than 5 hours was a significant risk factor for the development of prehypertension, whereas sleep time was not significantly associated with prehypertension.
Keywords: prehypertension; sleep duration; sleep time; undergraduate medical student; Kolkata